The Effect of Social Media Promotion and Online Consumer Reviews on Purchas Decisions with Mediation of Consumer Trust on Coffee Shop Tentang Kopi Medan - Mahbub, Moehammad Rizki; Rini, Endang Sulistya; Absah, Yeni (KnE Social Sciences, 2024)
Through customer trust as an intervening variable in coffee shops regarding coffee, this study intends to evaluate and assess the direct and indirect effects of social media marketing and online consumer evaluations on purchase decisions. Associative research is the study of associations. Primary data were used for this research, Although this is not a limit to the study’s population, up to 125 samples could have been collected inadvertently. The data analysis method used is called path analysis. The analysis of the data was done via SPSS. The study’s conclusions show that social media marketing affects consumer trust directly, favorably, and significantly, whereas online customer reviews and social media promotion have an analogous impact. Keywords: social media promotion, online consumer review, consumer trust, purchase intention